Sedimentation velocity studies of the high–molecular weight aggregates of the HIV gp41 ectodomain - Jacobs, Amy (Cold Spring Harbor Laboratory Press, 2004)
Accumulation of the HIV envelope protein gp41 is observed in the brain tissues of patients suffering from HIV-associated dementia. Previously, we have shown by electron microscopy that the extracellular domain of SIV gp41, which is analogous to that of HIV, forms high–molecular weight aggregates in vitro, and we have postulated that such high–molecular weight aggregates are responsible for neurological damage in a manner similar to protein deposition diseases such as Alzheimer’s and the prion diseases. In this manuscript, we have characterized the self-association of the HIV gp41 ectodomain by sedimentation velocity. We show that discreet species of the gp41 high–molecular weight aggregates are present. The maximum population occurs at 20 S, which corresponds to ~5 trimers of gp41, suggesting that five trimers are required for nucleation of the high–molecular weight aggregates. The concentration dependence of the gp41 self-association indicates that it occurs by mass action. The temperature dependence of gp41 self-association suggests that it is driven by entropy, indicating that intermolecular hydrophobic interactions between trimers of gp41 are driving the association.